2013
DOI: 10.1128/cvi.00670-13
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Recombinant Protein-Based Enzyme-Linked Immunosorbent Assay for Diagnosis of Mycoplasma bovis Infection in Cattle

Abstract: Mycoplasma bovis causes a range of diseases in cattle, including mastitis, arthritis, and pneumonia. However, accurate serological diagnosis of infection remains problematic. The studies described here aimed to identify an antigen that might be used to develop a more specific and sensitive diagnostic assay. A 226-kDa immunogenic protein was consistently detected in Western blots by antibodies in sera from calves experimentally infected with M. bovis. This protein was shown to be a membrane protein with lipase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
110
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(111 citation statements)
references
References 34 publications
1
110
0
Order By: Relevance
“…It was indicated that the identification of M. bovis strains in cattle herds and the evaluation of their pathogenicity and antigenic variation is important (Behrens et al, 1994). P48 is a membranous lipoprotein of 48kDa weight that is homologous to the family of the Macrophage Activator Lipoproteins (MALPs) and is coded via a conserved sequence specific to the M. bovis species (Wawegama et al, 2014). As the P48 gene is a conserved sequence in all M. bovis strains, designed primers by Fu (Fu et al, 2014), were used for amplification the P48 gene in this study.…”
Section: Mycoplasmamentioning
confidence: 99%
See 1 more Smart Citation
“…It was indicated that the identification of M. bovis strains in cattle herds and the evaluation of their pathogenicity and antigenic variation is important (Behrens et al, 1994). P48 is a membranous lipoprotein of 48kDa weight that is homologous to the family of the Macrophage Activator Lipoproteins (MALPs) and is coded via a conserved sequence specific to the M. bovis species (Wawegama et al, 2014). As the P48 gene is a conserved sequence in all M. bovis strains, designed primers by Fu (Fu et al, 2014), were used for amplification the P48 gene in this study.…”
Section: Mycoplasmamentioning
confidence: 99%
“…Traditional methods of detection and isolation of Mycoplasma strains such as serological and culture methods are time consuming, so the more sensitive biological methods such as PCR, are widely used for the detection and molecular analysis of various bacteria such as M. bovis strains in every microbial laboratories worldwide (Kirk and Lauerman, 1994). P48 is a membranous lipoprotein of slightly lower than 48kDa that is homologous to the family of the Macrophage Activator Lipoproteins (MALPs) and it is coded via a conserved sequences specific to the M. bovis species (Wawegama et al, 2014), so the sequence of M. bovis strain PG45 under accession number of CP002188 was selected (Wise et al, 2011) to compare with the strains detected in this study. The encoding gene sequence of lipoprotein P48 is recorded as accession numbers of DQ020481 and DQ020482 at Gene Bank (Lysnyansky et al, 2008) and it is known as one of the virulence factors of M. bovis species (Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis by the authors revealed that the milA protein contained a membrane spanning region at its amino terminal end, with the remainder of the protein predicted to be located extracellularly (Wawegama et al, 2014). Homologues were found in both Hubei-1 and HB0801 M. bovis strains for which complete genome sequences are available, as well as M. agalactiae strains 5632 and PG2 (Wawegama et al, 2014).…”
Section: Protein Milamentioning
confidence: 99%
“…More recently, a novel 226 kDa protein encoded by the milA gene (MBOVPG45_0710) was characterised from the M. bovis field strain 3683 and investigated for use in the sero-diagnosis of experimental M. bovis infections in calves in Australia (Wawegama et al, 2014). Analysis by the authors revealed that the milA protein contained a membrane spanning region at its amino terminal end, with the remainder of the protein predicted to be located extracellularly (Wawegama et al, 2014).…”
Section: Protein Milamentioning
confidence: 99%
See 1 more Smart Citation